RETHINKING ISLAM THROUGH INTERNALIZATION OF INSIGHTS INTO ISLAMIC UNIVERSALITY IN ISLAMIC THEOLOGY - Asnan Purba; Akhmad Jazuli Afandi (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2022)
This article seeks to discuss the renewal of thought into a Muslim (internal renewal) through the internalization of universal insights in Islam. Islamic declarations and statements are universal and flexible to the demands of the times will be realized through understanding and understanding of Islam itself in a kaffah (comprehensively). This research is a conceptual study by utilizing sources of literature. The author will review data from the source of the library with various points of view to determine the value of Islamic universality, including in terms of theology, law, humanity, anthropology, and psychology. The author will carry out internalization efforts through the cultivation of a strong understanding of insight into Islam. Thus a Muslim will be able to renew the pattern of thinking precisely according to the purpose because renewal without insight is nonsense.Keywords: Islam; universal insight; Islamic thought; Internalization.